Jamaica : Request for Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report, 2020)
This paper discusses Jamaica's Request for Purchase Under the Rapid Financing Instrument (RFI). The Jamaican authorities have proactively responded to the coronavirus disease 2019 (COVID-19) pandemic. Nevertheless, despite the authorities' best efforts, the pandemic is severely impacting the Jamaican economy, as a sudden stop in tourism and falling remittances are generating a sizable balance-of-payments need. Moreover, the economic outlook remains subject to an unusually high degree of uncertainty. The disbursement under the RFI will strengthen reserves and help catalyze additional support from other international financial institutions and development partners. The authorities' policy response to the COVID-19 crisis is appropriate, including the timely adoption of targeted measures to support jobs and provide resources to vulnerable segments of the population. Once the crisis abates, building on their demonstrated commitment to reform and stability-oriented measures, the authorities should continue the implementation of their ambitious reform agenda to support the economic recovery and ensure strong and sustainable economic growth.